High resolution temporal bone computerized tomography in paediatric sensorineural hearing loss prior to cochlear implantation - Rafiq, Suhail; Shafi, Fahad; Mohiuddin, Ajaz; Dar, Sajjad A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Congenital sensorineural hearing loss (SNHL) is one of the most common birth defects with incidence of approximately 1:1000 live births. Imaging plays an important role in the work up of cochlear implant candidates not only to identify inner ear congenital and acquired abnormalities or cochlear nerve anomalies but also to detect temporal bone abnormalities or variations that may alter surgical approach. Preoperative evaluation of cochleovestibular anatomy is an important component of the cochlear implant evaluation. The objective of the study was high resolution computerized tomography (HRCT) assessment of congenital ear anomalies before cochlear implantation. Methods: This prospective study was conducted in the Department of Radio diagnosis and Imaging, GMC, Srinagar. 24 children in the age group of 1 to 12 years with unidentiﬁed causes of bilateral SNHL were subjected to HRCT over a period of 7 months from January to July 2019. Results: Eighteen patients had normal radiological scans and 6 had congenital anomalies. We had one each case of common cavity, bilateral labrynthine aplasia, incomplete partition type 1, Mondini’s deformity with dilated vestibular duct, Internal auditory canal stenosis and bilateral large vestibular aqueduct. Out of 18 patients without congenital anomaly, two had Korner’s septum and giant jugular bulb which were important for operating surgeon. Conclusions: HRCT temporal bone is superior at identifying the bony labyrinth, including enlarged vestibular aqueduct and caliber of internal auditory canal. HRCT temporal bone should be supplemented by magnetic resonance imaging especially for cochlear nerve assessment. It is the initial imaging modality of choice for assessment of congenital SNHL.